DIMENSI TEOLOGI PENDIDIKAN ISLAM DALAM AL-QUR’AN - Muhibuddin Hanafiah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
Affective aspect (attitude) and psychometric aspect (behavior) ineducation practices, which are pragmatically nuanced, arefrequently ignored offhand. Practically, education very preferscognitive aspect (knowledge). While in fact, those three domainsare holistically integrated. They are cannot be separated one fromothers. The output measurement in educational process is notdetermined through one aspect only, intensity of cognitive aspect.Also, the attitude and behavior reflections as integral part ofpersonality are very decisive. This article tries to discuss aboutone of sub-aspect of the affective aspect, that is internalization oftheological values into paradigm of Islamic education. The articleis written by using library research which is analyzed byemploying deductive methodology and theological philosophicalmethodology that are based on the framework of ‚descriptiveanalysis‛ toward all related